Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1556-4029.2010.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Heteroplasmy in Hair: Study of Mitochondrial DNA Third Hypervariable Region in Hair and Blood Samples*

Abstract: Mitochondrial DNA (mtDNA) analysis has proved useful for forensic identification especially in cases where nuclear DNA is not available, such as with hair evidence. Heteroplasmy, the presence of more than one type of mtDNA in one individual, is a common situation often reported in the first and second mtDNA hypervariable regions (HV1/HV2), particularly in hair samples. However, there is no data about heteroplasmy frequency in the third mtDNA hypervariable region (HV3). To investigate possible heteroplasmy hots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Studies of the human CR show that the abundance of length variants of heteroplasmic polynucleotide regions often varies within and among tissues in individuals [3,6,10,11]. In contrast to human mtDNA studies, an intra-individual comparison of DNA from five hair shafts and one buccal swab of 16 dogs displayed inter-and intra-tissue stability of the ma/mi pCpTpC combinations.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Studies of the human CR show that the abundance of length variants of heteroplasmic polynucleotide regions often varies within and among tissues in individuals [3,6,10,11]. In contrast to human mtDNA studies, an intra-individual comparison of DNA from five hair shafts and one buccal swab of 16 dogs displayed inter-and intra-tissue stability of the ma/mi pCpTpC combinations.…”
Section: Discussionmentioning
confidence: 69%
“…As studies of the human CR have shown intra-individual sequence variation of heteroplasmic polyC stretches among and within tissues (e.g., [3,6,10,11]), it has also been recommended not to use length variation of these polynucleotide stretches as the sole reason to exclude DNA samples having the same maternal origin [6,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the mechanism that results in stutter products associated with nuclear DNA testing of short tandem repeat (STR) markers [19]. Similarly, stutter of the dinucleotide AC repeats at nps 515-524 of the mtDNA genome is observed as LHP [4,20,21]. Replication slippage can occur in vivo, but it also may arise during in vitro replication events including PCR amplification.…”
Section: Introductionmentioning
confidence: 61%